Boikot Barang Israel: Strategi Perlawanan Dan Solidaritas Global Dalam Mendukung Perjuangan Palestina - Anne Margareth; Dandi Bintang; Desi Natalia; Dewi Sartika Siregar; Dwi Agus Pranata; Rini Armianti Berutu; Yemima Nurhaida Sryagnes Batubara (Universitas Palangka Raya, 2024)
One of the main reasons behind the boycott of Israeli goods is to condemn Israeli actions that are considered to violate international law and human rights in the Palestinian territories. Boycotting Israeli goods is also a political and economic resistance strategy used by many countries and international organizations to support a sustainable peace solution between Israel and Palestine. By pressing Israel economically. This research is in accordance with the descriptive qualitative method with a library approach. Qualitative research was chosen as the type of research used in this research. The choice of qualitative research is because there are several factors that take precedence in terms of elaborating and explaining a phenomenon to be studied. In qualitative research there is also more explanation, description and analysis using an inductive approach. The data collection techniques used by researchers are techniques from relevant sources. In this case, the focus of various in-depth reference sources is the presence of key informants who have previously been given access to provide in-depth questions related to the topic of the problem being researched. The direct economic impact of the boycott has broader social and political impacts including increased international awareness of the Palestine-Israel issue, increased polarization, and political responses from governments and societies around the world.